What designers of an Innovative Learning Environment should know about I.R.4.0 and its impact on Spatial Design. - Almawaldi, Muna Khaled; Sharif, Roslina (MAJ - Malaysia Architectural Journal, 2020)
The aim of this paper is to study the relationship between the global changes of the fourth industrial revolution (I.R.4.0) and how it affected the learning environment. Understanding this relationship could help architects and designers to design innovative learning spaces that responds to the changes in the needs of education and the users. This paper outlines the many important phases of I.R.4.0 and how it affected our lives and changed our needs and ways of learning. Subsequently, the design of learning environments should respond accordingly in order to adapt to these changes. These changes are part of the Malaysia Education Blueprint 2015-2025 for Higher Education, which states its goal as to focus on improving the learning outcomes rather that inputs. In addition, it also aims to integrate technologies and learning innovations to improve and personalize the learning experience in order to respond to the needs of the students. The findings of this paper will help architects and designers to understand the new types of learning styles and trends and therefore design a learning space that can serve these trends and other future learning styles.